Meningkatkan Partisipasi Siswa dalam Proses Belajar dengan Media Pembelajaran Interaktif Wordwall dan Canva - Dewi, Sofia; Anggraeni, Tiara; Desrian, Wanda Novianti; Sudrajat, Juan Wendi (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
This community engagement program aims to enhance student participation in learning by utilizing interactive media, Wordwall and Canva. The lack of focus and engagement among students in the learning process has been a major challenge at SDN Cantel Margaasih Vilage. As a solution, interactive learning technology was implemented to create a more engaging learning experience. This program involved 89 students from grades IV and VI and was conducted through observation, interviews, and documentation. The evaluation results indicate that most students were more enthusiastic when using Wordwall compared to conventional methods. However, the limitation of audio features in Wordwall was identified as a challenge. These findings provide valuable insights for educators to optimize technology-based learning media to increase student engagement.